Public Transportation Strategy in Response to Covid-19 - Farizd, Miftah; Wahyuni, Chatarina Umbul; Yamani, Laura Navika (International Journal Labs, 2023)
The COVID-19 pandemic has had a significant impact on public transportation worldwide. At the beginning of the pandemic, public transportation systems reduced their performance by 80-90% in major cities in China, Iran, and the United States, and by 70% in the UK, including a significant decline in Indonesia. Several studies have shown that public transportation contributes significantly to the spread of the COVID-19 virus. This study aims to review the use of public transportation during the COVID-19 pandemic. Method: A systematic review using the PRISMA guidelines was conducted on literature published between 2020-2023 with inclusion criteria of national and international research articles in English related to the title